Hope and Religiosity as Determinants of Subjective Well-Being among Students at the Islamic Boarding School - Dewi, Rizma Kumala; Kusumaputri, Erika Setyanti; Abdulwahid, Kasmil S. (International Journal of Islamic Educational Psychology, 2024)
The inability to overcome academic challenges in boarding schools may lead to adverse health outcomes and negatively impact students' subjective well-being. One potential approach to enhance subjective well-being is through the cultivation of hope and religiosity. The purpose of this study is to prove the relationship between hope and religiosity on the subjective well-being of students. The research was conducted using quantitative methods with the help of the SPSS application. The sample was selected through cluster random sampling with the criteria of students who also live in Islamic boarding schools and are 18–25 years old. A Likert-scale questionnaire was administered to 334 students to collect data. The research location is in the Special Region of Yogyakarta. The instruments used in this study include the Satisfaction of Life Scale (SWLS), the Positive and Negative Affect Scale (PANAS), the Hope Scale, and the Religiosity Scale. The final analysis for the hypothesis test was carried out by multiple linear regression analysis, which had previously been carried out in prerequisite tests. The results indicated that the three hypotheses were supported, demonstrating a significant and positive correlation between hope and religiosity on the subjective well-being of Mahasantri. Furthermore, the two independent variables individually influenced the dependent variable. The practical contribution of hope and religiosity to subjective well-being was 40.2%, suggesting that these factors play a substantial role in enhancing the subjective well-being of students. The study revealed that the effect of hope (33.5%) was more pronounced than that of religiosity (17.8%), which can be attributed to hope possessing two crucial aspects in goal attainment that religiosity lacks: the development of planning and the capacity for self-motivation.